Development of Android-Based Interactive Learning Media to Facilitate the Flipped Classroom Learning Model - Vina Cahya Farhani; Satya Santika; Eva Mulyani (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
The urgency of developing learning media in the flipped classroom lies in the need for digital tools that can facilitate pre-class independent learning, as existing media are generally linear and lack interactivity. This study aims to develop interactive Android-based learning media called Math Venture Algebra to support ninth-grade junior high school algebra learning through the flipped classroom model. The development was carried out using an R&D approach based on the ADDIE model (Analysis, Design, Development, Implementation, Evaluation), which is relevant because it provides a systematic process for designing interactive Android-based media. Data was collected through semi-structured interviews and questionnaires validated by two subject matter experts and two media experts, and tested on 30th grade students at Tasikmalaya State Junior High School 5. The instrument uses a Likert scale that has been tested for validity and reliability, while the data is analyzed descriptively. Math Venture Algebra media is designed with key features such as instructional videos, interactive exercises, quizzes, and adaptive navigation that support the pre-class flipped classroom phase, so that students can learn independently before face-to-face discussions. The results of the study show that this media is in the “highly feasible” category according to expert assessment, as well as “very practical” according to students with a practicality level of 87%. These findings confirm that Android-based interactive media integrated with the flipped classroom contributes to increased independence, engagement, and quality of mathematics learning, while enriching 21st-century technology-based educational practices.